Prolonged QT dispersion in inflammatory bowel disease - Yorulmaz, Elif (Baishideng Publishing Group Co., Limited, 2013)
AIM: To investigate the frequency and factors of prolonged QT dispersion that may lead to severe ventricular arrhythmias in patients with inflammatory bowel disease (IBD). METHODS: This study included 63 ulcerative colitis (UC) and 41 Crohn’s disease (CD) patients. Forty-seven healthy patients were included as the control group. Heart rate was calculated using electrocardiography, corrected QT dispersion (QTcd) and the Bazett’s formula. Homeostasis model assessment (HOMA) was used to determine insulin resistance (IR). HOMA values < 1 were considered normal and values > 2.5 indicated a high probability of IR. RESULTS: Prolonged QTcd was found in 12.2% of UC patients, and in 14.5% of CD patients compared with the control group (P < 0.05). A significant difference was found between the insulin values (CD: 10.95 ± 6.10 vs 6.44 ± 3.28, P < 0.05; UC: 10.88 ± 7.19 vs 7.20 ± 4.54, P < 0.05) and HOMA (CD: 2.56 ± 1.43 vs 1.42 ± 0.75, P < 0.05; UC: 2.94 ± 1.88 vs 1.90 ± 1.09, P < 0.05) in UC and CD patients with and without prolonged QTcd. Disease behavior types were determined in CD patients with prolonged QTcd. Increased systolic arterial pressure (125 ± 13.81 vs 114.09 ± 8.73, P < 0.01) and age (48.67 ± 13.93 vs 39.57 ± 11.58, P < 0.05) in UC patients were significantly associated with prolonged QTcd. CONCLUSION: Our data show that IBD patients have prolonged QTcd in relation to controls. The routine follow-up of IBD patients should include determination of HOMA, insulin values and electrocardiogram examination.